Effect of zirconia substructure thickness on the mechanical properties and adhesion of veneering porcelain - Daniel Lungareze; Giovanni Cunha; Eduardo Mariscal Muñoz; Renata Garcia Fonseca; Gelson Adabo (Universidade Estadual de Campinas, 2019)
Aim: This study investigated the influence of yttrium-stabilized tetragonal zirconia polycrystals (Y-TZP) thickness on fracture load of porcelain-veneered crowns (FL), fracture toughness of porcelain (FT), and the shear bond strength zirconia/porcelain (SBS). Methods: Artificial first molar was prepared for full crown (N=45) with different occlusal reduction. Y-TZP cores were made with different thickness at the occlusal face (1mm, 2mm and 3mm) (n=15). The cores were veneered with VM9 - Vita porcelain with 1.0 mm layer. For FL testing, axial load was applied to the mesiolingual cusp of the crowns.  For FT testing, flat Y-TZP plates (5X5 mm) with 1, 2 or 3 mm thickness were veneered with 1.0 mm porcelain layer (n=10). FT by indentation fracture technique was measured close to the interface and at the top surface. For SBS by knife-edge shearing rod, cylindrical porcelain with 5 mm in diameter and 3 mm was applied on flat Y-TZP plates (1, 2 and 3 mm thickness) (n = 10). Results: Data analyzed by 1-Way ANOVA for FL of crowns and SBS between Y-TZP and porcelain were not significant. Two-way ANOVA for FT was significant for zirconia thickness and measurement area. The post-hoc test showed higher values for the groups with 2 and 3mm, and higher values at the interface, irrespectively of Y-TZP thickness. Conclusion: The zirconia thickness did not affect the FL of veneered crowns and the SBS between the ceramics, but FT of porcelain was lower in thinner zirconia substructure and close to the interface Y-TZP/Porcelain.